Radiological Comparison of the Lacrimal Sac Fossa Anatomy Between Black Africans and Caucasians. Issue 4 (July 2015) - Gore, Sri K.; Naveed, Hasan; Hamilton, Jane; Rene, Cornelius; Rose, Geoffrey E.; Davagnanam, Indran
Abstract : Purpose: To compare, in black Africans and Caucasians, the radiological anatomy of the intranasal structures and lacrimal sac fossa as relevant to dacryocystorhinostomy. Methods: 0.75 mm section cranio-orbital computed tomography scans from 72 patients (42 black Africans and 30 Caucasian) were included in this retrospective observational case series. Only one orbit from each scan was utilized. The main outcome measures were: the thickness and proportions of the lacrimal bone and frontal process of the maxilla evaluated at 3 axial planes (upper, middle, lower) in the lacrimal sac fossa; 2 measurements of maxillary thickness were obtained at each plane—namely, the "midpoint thickness" and the "maximum thickness." The anterior extent of the nasal mucosa was also evaluated. Results: The frontal process of the maxilla was thickest inferiorly ( p < 0.001) and the maximum maxillary thickness was significantly thicker in black Africans as compared with Caucasians ( p < 0.001) at all planes. At midfossa level, the proportion of maxillary bone forming the lacrimal fossa wall was significantly greater in black Africans ( p < 0.01). In contrast, the length of nasal mucosa available for creation of an anastomosis, as estimated from the greatest mucosal height, was significantly greater in Caucasians ( p < 0.01). Conclusions: Black Africans have a lacrimal sac fossa bounded by thicker maxillary bone, this bone constituting a higher proportion of the fossa wall at its midpoint, and also have significantly less nasal mucosa available for soft-tissue anastomosis during lacrimal drainage surgery. The anterior lacrimal crest, comprising the frontal process of the maxilla, was thickest at the lowest plane in both black Africans and Caucasians. Abstract : The authors compared radiological anatomy of the nasal mucosa and lacrimal sac fossa in black Africans and Caucasians, as relevant to dacryocystorhinostomy, identifying significant bony and nasal mucosal differences